Нечітка сегментація зображень на основі теорії достовірності - Магніцький, Є. Д. (ХНУРЕ, 2024)
Computational intelligence methods are widely used to solve many complex problems, including, of course, traditional: Data Mining and such new directions as Dynamic Data Mining, Data Stream Mining, Big Data Mining, Web Mining, Text Mining, etc. In the paper was proposed new on-line method of fuzzy clustering-segmentation of data streams based on credibilistic approaches
Keywords: сегментація зображень